Probiotic Potential of Leuconostoc pseudomesenteroides and Lactobacillus Strains Isolated From Yaks - Wang, Yaping; Li, Aoyun; Jiang, Xiong; Zhang, Hui; Mehmood, Khalid; Zhang, Lihong; Jiang, Jinhuan; Waqas, Muhammad; Iqbal, Mujahid; Li, Jiakui (Frontiers in Microbiology, 2018)
The purpose of this study was to evaluate the antibacterial activity and safety of bacterias with probiotic potential isolated from free-ranging Tibetan yaks in high altitude regions of Tibet. For this purpose, one Leuconostoc pseudomesenteroides strain (named P1) and two Lactobacillus johnsonii and Lactobacillus mucosae strains (named LY1 and LY2) respectively were isolated from fecal samples of Tibetan yaks. The antibacterial activity of the isolates was studied using Escherichia coli (E. coli ATCC 25922), Staphylococcus aureus (S. aureus ATCC 26112) and Salmonella enteritidis (S. enteritidis NCTC 13349) as indicator pathogens. The results showed that LY1 had high antibacterial efficacy against E. coli and S. enteritidis, while P1 had the most powerful bacteriostatic ability against S. aureus. PCR amplification showed that all the isolated strains were positive for Ent P2 (enterocin P-like bacteriocin) and exhibited a high tolerance to bile and low pH. Moreover, the safety of P1, LY1 and LY2 was determined through antibiotic resistance experiments, resistance gene testing, and hemolytic analysis while the antibacterial activity was assessed by in vitro and in vivo experiments. The LY2 strain was abandoned as a potential probiotic due to the detection of the vanA gene. The mice were fed from days 1 to 30 in six groups, the P1-1 (gavaged with P1 1×108CFU/day), P1-2 (gavaged with P1 1×109CFU/ day), LY1-1 (gavaged with LY1 1×108CFU/ day), LY1-2 (gavaged with LY1 1×109CFU/ day), control (gavaged with an equal volume of vehicle), and blank control (gavaged with an equal volume of vehicle) groups. After 30 days, mice in all groups were intraperitoneal challenged with 1×108CFU of E. coli (n=10) in the abdomen. After two days of infection, the mice in the control group showed more severe damage in the liver, spleen and intestine than the mice in the P1-2 and LY1-2 groups. The mice in the P1-2 and LY1-2 groups had lower rates of diarrhea and mortality than other groups. In conclusion, bacteria with probiotic potential isolated from yaks may possibly be effective and safe antibacterial substances, providing a new treatment method to reduce the incidence of diarrhea associated with bacterial diseases in yaks.